2007
DOI: 10.1523/jneurosci.4006-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

K+Channel Facilitation of Exocytosis by Dynamic Interaction with Syntaxin

Abstract: Kv channels inhibit release indirectly by hyperpolarizing membrane potential, but the significance of Kv channel interaction with the secretory apparatus is not known. The Kv2.1 channel is commonly expressed in the soma and dendrites of neurons, where it could influence the release of neuropeptides and neurotrophins, and in neuroendocrine cells, where it could influence hormone release. Here we show that Kv2.1 channels increase dense-core vesicle (DCV)-mediated release after elevation of cytoplasmic Ca 2ϩ . Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(90 citation statements)
references
References 57 publications
(63 reference statements)
4
85
1
Order By: Relevance
“…In these experiments, we also confirmed the described association of syntaxin and Kv2.1 (Fig. 3A) (47)(48)(49). The increased CaMKII signal in Kv2.1-expressing cells could be the result of a direct interaction of the kinase with the K + channel.…”
Section: Injurious Oxidant Exposure Leads To Camkii Activation In Neusupporting
confidence: 85%
See 1 more Smart Citation
“…In these experiments, we also confirmed the described association of syntaxin and Kv2.1 (Fig. 3A) (47)(48)(49). The increased CaMKII signal in Kv2.1-expressing cells could be the result of a direct interaction of the kinase with the K + channel.…”
Section: Injurious Oxidant Exposure Leads To Camkii Activation In Neusupporting
confidence: 85%
“…CaMKII has been shown to regulate exocytosis via a specific interaction with syntaxin (43)(44)(45)(46). In addition, syntaxin is known to bind to the most proximal region of the Kv2.1 C terminus, termed C1a, during Ca 2+ -facilitated exocytosis in pancreatic and other nonneuronal cells (47)(48)(49). Importantly, we showed that syntaxin is also required for the membrane insertion of Kv2.1 channels during apoptosis (23).…”
Section: Injurious Oxidant Exposure Leads To Camkii Activation In Neumentioning
confidence: 70%
“…Constructs, adenoviruses and recombinant peptides The Kv2.1 pore mutant (Kv2.1 W365C/Y380T ) and construct lacking the syntaxin-binding domain (Kv2.1 W365C/Y380T ΔC1a) have been described previously [20] (Fig. 1a).…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion of 5% glycerol in the final wash minimised the non-specific interactions between syntaxin 1A and protein A-sepharose beads. The bound GST-fusion proteins were eluted with reduced glutathione as described [20]. For controls, cell lysates were immunoprecipitated with an irrelevant antibody (IgG) and with protein A-sepharose alone, or by performing the immunoprecipitation with Kv2.1 antibody in the presence of its antigen peptide (1:1 ratio).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation